DISTRIBUTION OF GOAT FASCILIOSIS IN THE IRRIGATED AREAS OF SURKHONDARYO PROVINCE - Hazratqulov I. A.; Taylakov T. I. (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the distribution of fasciola among goats in the irrigated areas of Surkhandarya region is studied. According to the results of the conducted scientific research, it was found that 20.5% of goats with fasciolosis in Surkhandarya region are affected by F.hepatica and 31.5% by F.gigantica.